Synthesis, Characterization, Molecular Docking Studies and Pharmaceutical Evaluation of some Novel [1,2,4]Triazolo[3,4-B][1,3,4]Thiadiazole - Mekky, Athraa Hameed; Hamed, Fadil M.; Hassan, Bassam A. (Jurnal Kimia Valensi, 2024)
A new series of fused [1,2,4]Triazolo[3,4-b][1,3,4]thiadiazole 4a-4e have been synthesized by many steps. Firstly, benzohydrazide [1] has been synthesized from the reaction of methyl benzoate with hydrazine hydrate. Secondly, the cyclization reaction of benzohydrazide with carbon disulfide in the presence of potassium hydroxide produced 5-phenyl-1,3,4-oxadiazole-2-thiol[2]. Thirdly,5-phenyl-1,3,4-oxadiazole-2-thiol[2] was treated with potassium hydroxide using pyridine to give 4-amino-5-phenyl-4H-1,2,4-triazole-3-thiol. Finally, the fused [1,2,4]Triazolo[3,4-B][1,3,4]Thiadiazole 4a-4e   were synthesized from the reaction of 4-amino-5-phenyl-4H-1,2,4-triazole-3-thiol[3], with various aromatic aldehydes. The structures of the newly synthesized compounds have been confirmed based on spectral studies. The new novel compounds exhibited anticancer activity docking with C-Met tyrosin kinase receptor as shown by their docking scores ranging between -3.506 to -4.468 Kcal/mol as compared to standard crizotinib binding affinity is to -3.211Kcal/mol for anticancer efficiency. The newly synthesized triazole thiadiazole derivatives were evaluated for their in-vitro cytotoxic activity against human cancer cell lines. It was found that compounds 4b and 4c showed higher cytotoxicity against the MCF-7 cell line and no cytotoxic effect on normal cell line HdFn.